2021
DOI: 10.3390/microorganisms9030644
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Probiotics Improve Fermentation Quality, Microflora Phenotypes, and Trophic Modes of Fermented Vegetable Waste for Animal Feed

Abstract: The fermentation of leaf vegetable waste to produce animal feed reduces the environmental impact of vegetable production and transforms leaf vegetable waste into a commodity. We investigated the effect of exogenous probiotics and lignocellulose enzymes on the quality and microbial community of fermented feed (FF) produced from cabbage waste. The addition of exogenous probiotics resulted in increased crude protein (CP) content (p < 0.05), better odor (moderate organic acid and ethanol, with low ammonia-N, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…These samples also contained more lactic acid bacteria, higher lactic acid contents, lower pH, lower mold content, and higher aerobic stability (p < 0.05). This result is similar to that of Du et al [ 14 ] for the production of fermented feed from cabbage waste, indicating that exogenous probiotic inoculation is a promising strategy to enhance the bioconversion of food waste to animal feed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These samples also contained more lactic acid bacteria, higher lactic acid contents, lower pH, lower mold content, and higher aerobic stability (p < 0.05). This result is similar to that of Du et al [ 14 ] for the production of fermented feed from cabbage waste, indicating that exogenous probiotic inoculation is a promising strategy to enhance the bioconversion of food waste to animal feed.…”
Section: Discussionsupporting
confidence: 90%
“…Food waste fermentation is a complex process dominated by microbial community. Bacterial community analysis and metabolomic analysis of fermentation systems can provide important insights into animal health and welfare from the perspective of nutritional value, as well as important information that enables the screening of microorganisms that regulate food waste fermentation [ 14 , 29 ]. This study was the first to combine bacterial community and metabolomic analyses to elucidate the bacterial community and metabolome characteristics of fermentation products derived from commercial and laboratory-made bacteria inoculated with food waste from a centralized treatment facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Erawan et al, element N is involved in plant vegetative growth, nitrogen is an important ingredient for cell division and elongation, and so N is a component of protoplasm. According to Erawan et al (2013) [7], element N plays a role in plant vegetative growth, nitrogen is a necessary component for cell division and elongation, and so N is a constituent of protoplasm, which is widely distributed in tissues such as growing points.…”
Section: Plant Heightmentioning
confidence: 99%
“…The compositions of raw materials are shown in Table 1, and were measured following the procedure in Section 2.4. It was previously proved that homolactic fermentation and facultative anaerobic LP (CGMCC NO.19862) could improve the cabbage byproduct fermented feed; they were stored at -80 • C in our laboratory using strain preservation tubes with MRS medium containing 35% (v/v) glycerol [16]. The LP inoculation was prepared as Ren et al reported and the final cell concentration of inoculum was 3.3 × 10 8 CFU•mL −1 [2].…”
Section: Preparation Of Materials and Additivesmentioning
confidence: 99%